Peran Lingkungan Kerja Terhadap Produktivitas Karyawan pada Butik Rengganis Kota Bandung - Yanti, Alfina Dhama; Nugraha, Harry (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine and present an analysis of whether there is a positive influence between the work environment and employee productivity at the Rengganis boutique in Bandung. The type of research used is descriptive with a quantitative method. The author uses quantitative research because the data collection technique used involves questionnaires and statistical tools to process the questionnaires to determine whether there is a positive influence between the work environment and employee productivity at Rengganis Boutique. The results of the data analysis in this study indicate that there is a significant influence between the work environment and employee productivity. Based on the simple regression equation, where the regression coefficient value is 0.320, it indicates that the Work Environment has a positive influence on Employee Productivity. The coefficient of determination provided by the Work Environment variable on Employee Productivity is 85.9%, with the remaining 14.1% influenced by other factors not investigated in this study by the author. The t-test results show that if the calculated t-value is greater than the table t-value (9.554 > 2.110), it means there is a significant influence between the Work Environment and Employee Productivity at Rengganis Boutique, so the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected.